Prevention of vaccine-matched and mismatched influenza in children aged 6–35 months: a multinational randomised trial across five influenza seasons. (May 2018) - Claeys, Carine; Zaman, Khalequ; Dbaibo, Ghassan; Li, Ping; Izu, Allen; Kosalaraksa, Pope; Rivera, Luis; Acosta, Beatriz; Arroba Basanta, Maria Luisa; Aziz, Asma; Cabanero, Miguel Angel; Chandrashekaran, Vijayalakshmi; et al.
Summary: Background: Despite the importance of vaccinating children younger than 5 years, few studies evaluating vaccine prevention of influenza have been reported in this age group. We evaluated efficacy of an inactivated quadrivalent influenza vaccine (IIV4) in children aged 6–35 months. Methods: In this phase 3, observer-blinded, multinational trial, healthy children from 13 countries in Europe, Central America, and Asia were recruited in five independent cohorts, each in a different influenza season. Participants were randomly assigned (1:1) to either IIV4 (15 μg haemagglutinin antigen per strain per 0·5 mL dose; a single dose on day 0 for vaccine-primed children, and two doses, on days 0 and 28, for vaccine-unprimed children) or to one or two doses of a non-influenza control vaccine. Primary endpoints were moderate-to-severe influenza or all influenza (irrespective of disease severity) confirmed by RT-PCR on nasal swabs. Cultured isolates were further characterised as antigenically matched or mismatched to vaccine strains. Efficacy was assessed in the per-protocol cohort and total vaccinated cohort (time-to-event analysis), and safety was assessed in the total vaccinated cohort. Findings: Between Oct 1, 2011, and Dec 31, 2014, 12 018 children were recruited into the total vaccinated cohort (6006 children in the IIV4 group and 6012 children in the control group). 356 (6%) children in the IIV4 group and 693 (12%) children in the control group had at least one case of RT-PCR-confirmed influenza. Of these 1049 influenza strains, 138 (13%) were A/H1N1, 529 (50%) were A/H3N2, 69 (7%) were B/Victoria, and 316 (30%) were B/Yamagata. Overall, 539 (64%) of 848 antigenically characterised isolates were vaccine-mismatched (16 [15%] of 105 for A/H1N1; 368 [97%] of 378 for A/H3N2; 54 [86%] of 63 for B/Victoria; 101 [33%] of 302 for B/Yamagata). Vaccine efficacy was 63% (97·5% CI 52–72) against moderate-to-severe influenza and 50% (42–57) against all influenza in the per-protocol cohort, and 64% (53–73) against moderate-to-severe influenza and 50% (42–57) against all influenza in the total vaccinated cohort. There were no clinically meaningful safety differences between IIV4 and control. Interpretation: IIV4 prevented influenza A and B in children aged 6–35 months despite high levels of vaccine mismatch. Vaccine efficacy was highest against moderate-to-severe disease, which is the most clinically important endpoint associated with greatest burden. Funding: GlaxoSmithKline Biologicals SA.